An Analysis of Pronunciation Errors of English Consonant Sounds /tʃ/ and /dʒ/ by First-Year English Department Students - Naila Alvi Nuril Auliya; Andrian Nuriza Johan; Sri Widodo (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
English pronunciation plays an important role in achieving effective oral communication, yet many English as a Foreign Language (EFL) learners experience difficulties in producing English sounds that do not exist in their native language. Among these sounds, the English affricative consonants /tʃ/ and /dʒ/ are often problematic for Indonesian learners. Therefore, this study aimed to identify and analyze the pronunciation errors, particularly the substitution patterns, of the English affricative consonant sounds /tʃ/ and /dʒ/ produced by first-year English Education students. This research employed descriptive qualitative design supported by simple quantitative analysis. The participants were 17 first-year students selected through purposive sampling. Data was collected through a pronunciation test consisting of 20 words containing the target sounds in initial, medial, and final positions, and the students’ pronunciations were recorded in video form. The findings revealed a total of 39 pronunciation errors, all of which (100%) were classified as substitution errors. The sound /dʒ/ was more frequently mispronounced than /tʃ/. Pronunciation errors occurred in all sound positions, with the highest frequency found in the initial and medial positions (38.46% each), followed by the final position (23.08%). The dominant substitution patterns were /d/ /j/, /d/ /g/, /tʃ/ → /k/, and /tʃ/ → /s/. These findings indicate that students tended to replace English affricative consonants with more familiar non-affricative sounds. The study highlights the need for targeted pronunciation instruction and systematic drilling activities focusing on English affricative consonants to improve students’ pronunciation accuracy and communicative intelligibility.